Garbage in guano? Microplastic debris found in faecal precursors of seabirds known to ingest plastics - Provencher, J.F. (J. F.); Vermaire, J. (Jesse); Avery-Gomm, S. (S.); Braune, B.M. (Birgit M.); Mallory, M.L. (M. L.) (Science of The Total Environment, 2018)
Plastic pollution is global environmental contaminant. Plastic particulates break down into smaller fragments in the environment, and these small pieces are now commonly found to be ingested by animals. To date, most plastic ingestion studies have focused on assessing retained plastics or regurgitated plastics, but it is likely that animals also excrete plastic and other debris items. We examined the terminal portion of the gastrointestinal tract of a seabird known to commonly ingest plastics, the Northern Fulmar (Fulmarus glacialis), to determine if seabirds excrete microplastics and other debris via their guano. We also examine how guano collections may be used as an indicator of retained plastics. The frequency of occurrence of microplastics did not correlate between the gut and faecal precursor samples, but there was a positive relationship between th